PENGARUH TEKNOLOGI INFORMASI, PENGENDALIAN INTERN, GAYA KEPEMIMPINAN DAN GOOD GOVERNANCE TERHADAP KINERJA INSTANSI PEMERINTAH (STUDI EMPIRIS PADA SKPD KABUPATEN BENGKALIS) - Meilda Wiguna (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
The purpose of this sstudy is technology information, internal control, leadershipstyle, and good governance of the performance of government agencies at SKPDsBengkalis Regency.The research method used is descriptive research method withsurvey approach,the type of data used iss primary data, primary data by sendingquestionnaires directly to the respondents and take it back after a predeterminedtime period. The study population is SKPDs Bengkalis Regency. The sample wasechelons III and IV on bodies and agencies in Bengkalis Regency. The classicalassumption used is the test for normality, multicollinearity test and testheterokedastisitas. Hypothesis testing using Adjusted R square, Model analysis ofthe data used I multiple linear regression. Testing the quality of the data used arevalidity and reliability testing.Simultaneouss significant (Test-f), partialsignificance (Test-t), the hypothesis testing results show that the hypothesis first,second and third received, this suggests that information technology, internalcontrol and leadership style of the performance of government agencies at SKPDsBengkalis Regency.